2011
DOI: 10.1016/j.biortech.2011.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation of rhamnolipid production in Pseudomonas aeruginosa – A review

Abstract: Pseudomonas aeruginosa produces abundant levels of rhamnolipid biosurfactants which exhibit remarkable chemical and physical characteristics, making these compounds attractive targets for biotechnology research. The complex gene regulation network involved in rhamnolipids' biosynthesis represents a challenge to industrial production, which has been the object of a growing number of studies. This article provides a comprehensive review of the known gene regulatory factors involved in rhamnolipid production with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
138
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 76 publications
4
138
0
8
Order By: Relevance
“…Although cells exposed to carbenicillin exhibit a dramatic morphology change, we found that exposure to tobramycin, but not carbenicillin, resulted in profile shifts of both PQS and AQNO families during swarming. This is in contrast to reports that have suggested a general PQS response to antimicrobials (22,26,27). Our findings are consistent with the hypothesis that AQ modulations following tobramycin exposure during pre-biofilm swarming should contribute to antibiotic tolerance (22,25,38), however, other factors must control P. aeruginosa tolerance to carbenicillin.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although cells exposed to carbenicillin exhibit a dramatic morphology change, we found that exposure to tobramycin, but not carbenicillin, resulted in profile shifts of both PQS and AQNO families during swarming. This is in contrast to reports that have suggested a general PQS response to antimicrobials (22,26,27). Our findings are consistent with the hypothesis that AQ modulations following tobramycin exposure during pre-biofilm swarming should contribute to antibiotic tolerance (22,25,38), however, other factors must control P. aeruginosa tolerance to carbenicillin.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings reveal a role for the PQS subclass in response to tobramycin exposure, but not carbenicillin exposure. Thus, we conclude that the PQS stress response (22,27) is not a universal response mechanism to all antibiotics. Additionally, AQs belonging to the general PQS pathway appear to be under distinct regulatory control mechanisms, since modulations to the PQS and targeted AQNOs subclasses are observed to be independent of one another.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Biosurfactants production is known to be controlled by a sophisticated and highly organized regulatory network at both the transcriptional and post-transcriptional level (Dusane et al, 2010;Reis et al, 2011). Factors that were shown to play a key role in biosurfactants production include quorum sensing and stress conditions like nutrients deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, biosurfactants production increases under nitrogen-limiting conditions Reis et al, 2011). The nitrogen source indirectly affects the rhlAB operon via the nitrogen metabolism sigma factor regulator RpoN.…”
Section: Discussionmentioning
confidence: 99%